Analisis Sistem Pengendalian Internal Melalui Audit Berbasis Risiko (ABR) Oleh Aparat Pengawas Intern Pemerintah (APIP) Dalam Mencapai Target Rencana Pembangunan Jangka Menengah Daerah (RPJMD) Studi Kasus pada Inspektorat Kota Banjarbaru - - - Mujennah; Budi - Artinah (Universitas Kristen Maranatha, 2018)
This research explains the role of APIP in carrying out, its functions and duties to achieve the target of Regional Medium Term Plan (RPJMD) 2016-2020. Inspectorate of Banjarbaru City as an element of local government oversight is required to act as an institution capable of improving the quality of supervision on the way of regional development, so as to realize good governance and clean governance. Quoted from the RENSTRA Inspektorat Banjarbaru City there are still strategic issues that can hamper the implementation of the vision mission RPJMD mission in Inspectorate Banjarbaru City. These strategic issues include many findings and recommendations of the results of the investigation that have not been followed up, the lack of strict sanctions on the management of performance andinternal control is not good, the quality of public services should still be improved, supervision procedures have not run well, commitment and motivation APIP still needs to be improved. In addition, the Inspectorate of Banjarbaru City has limited resources so it must be able to work efficiently and effectively. as well as the non- implementation of Risk-Based Audit approaches for all functional functional officials. Through an effective internal control system and effective RSP audit implementation is expected to assist APIP's role in implementing the RPJMD 2016- 2020 to reduce strategic issues and mitigate risk to acceptable limits.Keywords:Risk Based Audit (RBA), Government Internal Control System (SPIP), Inspectorate, Good Governance(GC), Clean Governance (CG), Government Internal Supervisory Apparatus (APIP)